Hypothenemus hampei (Coleoptera: Curculionidae) as in vitro inducer of laminarinase and chitinase of Beauveria bassiana (Hypocreales: Clavicipitaceae). (2017)
In Peru, Hypothenemus hampei or the coffee berry borer, (CBB) is the most important pest, causing specific damage to coffee crops, because it causes fruit to fall during feeding. On the other hand, Beauveria bassiana is an entomopathogenic fungus widely used in biological control. This study determine the induction of chitinase and laminarinase of B. bassiana in presence of H. hampei powder and how it relates to pathogenicity in order to promote the development of biological control agents and replace the use of pesticides. Three different liquid media cultures were prepared to induce the enzymatic production and growth of B. bassiana; and biomass, total proteins, conidia, enzymatic activities and enzymatic specific activities were evaluated. Data were analyzed using SPSS 19.0. Significant differences (P < 0.05) for biomass (F = 5.30; df = 35; P < 0.05), conidia (F = 190.87; df = 35; P < 0.05), total proteins (F = 91.04; df = 35; p < 0.05), laminarinase activity (F = 27.61; df = 35; P < 0.05), specific laminarinase activity (F = 25.31; df = 35; P < 0.05), chitinase activity (F = 32.66; df = 35; P < 0.05) and specific chitinase activity (F = 26.91; df = 35; P < 0.05) were determined between each treatment evaluated. Levels of chitinase and laminarinase determined that induction of these enzymes is possible in liquid media cultures supplemented with powdered H. hampei extract. Results require further evaluation for application in vivo but are fundamental and constitute a contribution to knowledge about the pathogenic mechanism of B. bassiana.